The exiles in love - McKay, Hilary (New York : Margaret K. McElderry Books, 1998)
When Big Grandma takes the four Conroy sisters on holiday as a cure for the "family failing," the girls wonder if their grandmother herself is still susceptible to it.
"First published in 1996"--verso t.p.
Keywords: Sisters -- Fiction; Grandmothers -- Fiction; England -- Fiction